∫ 0 π 1 + cos 2 x x sin x d x
If the above integral can be written as C A π B , where A , B and C are positive integers with A and C being coprime integers. Find A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Definite Integrals
Let f ( x ) = 2 − x 2 x ⇒ I = ∫ 0 π x f ( sin x ) d x
Now using properties of definite integral, ∫ 0 a f ( x ) d x = ∫ 0 a f ( a − x ) d x I = ∫ 0 π x f ( sin x ) d x = ∫ 0 π ( π − x ) f ( sin ( π − x ) ) d x = ∫ 0 π ( π − x ) f ( sin x ) d x
Adding both the equations, I = 2 π ∫ 0 π f ( sin x ) d x
Now using the property ∫ 0 2 a f ( x ) d x = ∫ 0 a f ( x ) + f ( 2 a − x ) d x , we get I = π ∫ 0 π / 2 1 + cos 2 x sin x d x t = cos x , d t = − sin x d x = ∫ 0 1 1 + t 2 1 d t = π ( 4 π − 0 ) = 4 π 2
Note.
We can say generally that ∫ 0 π x f ( sin x ) d x = π ∫ 0 π / 2 f ( sin x ) d x
Good approach using the property.
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Definite Integrals
A substitution c o s x = t yields J = ∫ − 1 1 1 + x 2 c o s − 1 x d x
Since c o s − 1 ( − x ) = π − c o s − 1 x is valid when x ∈ ( − 1 , 1 ) so we have ,
J = 2 ∫ 0 1 1 + x 2 π d x − J ⟹ J = π [ t a n − 1 x ] 0 1 = 4 π 2
Thus the answer 2 + 4 + 1 = 7